Insights into the structure and morphogenesis of the giant basal spicule of the glass sponge Monorhaphis chuni - Andrzej Pisera; Magdalena Łukowiak; Sylvie Masse; Konstantin Tabachnick; Jane Fromont; Hermann Ehrlich; Marco Bertolino (Frontiers in Zoology, 2021)
Abstract Background A basal spicule of the hexactinellid sponge Monorhaphis chuni may reach up to 3 m in length and 10 mm in diameter, an extreme case of large spicule size. Generally, sponge spicules are of scales from micrometers to centimeters. Due to its large size many researchers have described its structure and properties and have proposed it as a model of hexactinellid spicule development. Thorough examination of new material of this basal spicule has revealed numerous inconsistencies between our observations and earlier descriptions. In this work, we present the results of detailed examinations with transmitted light and epifluorescence microscopy, SEM, solid state NMR analysis, FTIR and X-ray analysis and staining of Monorhaphis chuni basal spicules of different sizes, collected from a number of deep sea locations, to better understand its structure and function. Results Three morphologically/structurally different silica layers i.e. plain glassy layer (PG), tuberculate layer (TL) and annular layer (AL), and an axial cylinder (AC) characterize adult spicules. Young, immature spicules display only plain glassy silica layers which dominate the spicule volume. All three layers i.e. PG, TL and AL can substitute for each other along the surface of the spicule, but equally they are superimposed in older parts of the spicules, with AL being the most external and occurring only in the lower part of the spicules and TL being intermediate between AL and PG. The TL, which is composed of several thinner layers, is formed by a progressive folding of its surface but its microstructure is the same as in the PG layer (glassy silica). The AL differs significantly from the PG and TL in being granular and porous in structure. The TL was found to display positive structures (tubercles), not depressions, as earlier suggested. The apparent perforated and non-perforated bands of the AL are an optical artefact. The new layer type that we called the Ripple Mark Layer (RML) was noted, as well as narrow spikes on the AL ridges, both structures not reported earlier. The interface of the TL and AL, where tubercles fit into depressions of the lower surface of the AL, represent tenon and mortise or dovetail joints, making the spicules more stiff/strong and thus less prone to breaking in the lower part. Early stages of the spicule growth are bidirectional, later growth is unidirectional toward the spicule apex. Growth in thickness proceeds by adding new layers. The spicules are composed of well condensed silica, but the outermost AL is characterized by slightly more condensed silica with less water than the rest. Organics permeating the silica are homogeneous and proteinaceous. The external organic net (most probably collagen) enveloping the basal spicule is a structural element that bounds the sponge body together with the spicule, rather than controlling tubercle formation. Growth of various layers may proceed simultaneously in different locations along the spicule and it is sclerosyncytium that controls formation of silica layers. The growth in spicule length is controlled by extension of the top of the axial filament that is not enclosed by silica and is not involved in further silica deposition. No structures that can be related to sclerocytes (as known in Demospongiae) in Monorhaphis were discovered during this study. Conclusions Our studies resulted in a new insight into the structure and growth of the basal Monorhaphis spicules that contradicts earlier results, and permitted us to propose a new model of this spicule’s formation. Due to its unique structure, associated with its function, the basal spicule of Monorhaphis chuni cannot serve as a general model of growth for all hexactinellid spicules.